2017
DOI: 10.1017/s0033291717003142
|View full text |Cite
|
Sign up to set email alerts
|

White matter abnormalities in 22q11.2 deletion syndrome patients showing cognitive decline

Abstract: Within 22q11DS, the early cognitive decline is associated with microstructural differences in white matter. At the mean age of 17.8 years, these changes are reflected in increased FA in several tracts. We hypothesize that similar brain alterations associated with cognitive decline take place early in the trajectory of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…These microstructural changes were not seen in those without cognitive decline. 50 Microstructural white matter changes in individuals with 22q11.2 deletion syndrome were associated with lower axonal integrity, whereas in individuals without deletion at ultra-high risk for psychosis, such changes were suggestive of abnormal myelination. 49 Together, these data provide strong evidence that the 22q11.2 deletion has profound effects on brain structure in children and adults.…”
Section: Imaging Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…These microstructural changes were not seen in those without cognitive decline. 50 Microstructural white matter changes in individuals with 22q11.2 deletion syndrome were associated with lower axonal integrity, whereas in individuals without deletion at ultra-high risk for psychosis, such changes were suggestive of abnormal myelination. 49 Together, these data provide strong evidence that the 22q11.2 deletion has profound effects on brain structure in children and adults.…”
Section: Imaging Studiesmentioning
confidence: 98%
“…Some diffusion tensor imaging studies that have been done in individuals with 22q11.2 deletion syndrome found evidence for altered myelin and axon integrity in multiple tracts, some of which have been implicated in neuropsychiatric disorders. [48][49][50] Studies using rs-fMRI reported a global decrease in functional connectivity. 51,52 Preliminary results from the ENIGMA-22q working group, who collected the largest data set on 22q11.2 deletion syndrome to date, suggest lower diffusivity in individuals with 22q11.2 deletion syndrome than in healthy controls, possibly because of smaller axonal diameter.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Importantly, multivariate modeling revealed very consistent and widespread patterns of brain alterations, in line with recent evidence indicating that white matter alterations of first-episode and chronic stages of schizophrenia are very diffuse and affect the brain on a global level 9,38,39 . While studies have also demonstrated an involvement of white matter alterations in preclinical high-risk stages of psychosis in the general population 8 and in patients with 22q11.2DS presenting psychotic symptoms 19,[34][35][36] or a cognitive decline 37 , results were heterogeneous and prevented the identification of a reliable biomarker, likely because of the variability and small magnitude of premorbid anomalies. Current evidence suggests that, on the other hand, a multivariate assessment of brain structure can effectively identify early, more subtle patterns of alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from univariate studies that investigated white matter microstructure in patients with 22q11.2DS presenting psychotic symptoms 19,[34][35][36] or a cognitive decline 37 , the impact of the above-mentioned risk factors on white matter maturation remains largely unknown. Evidence increasingly shows that white matter alterations associated with psychosis are widespread and subtle 38,39 , suggesting that multivariate approaches may be better suited to capture the complex nature of brain alterations related to premorbid stages.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of supernumerary neurons within the white matter of the subcortical region is a commonly observed anomaly of ASD. Additionally, white matter integrity as measured by fractional anisotropy seems to be altered in 22q11.2 deletion patients [97] and 16p11.2 deletion is also associated with decreased myelination in the subcortical region of the brain [98]. A recent animal study of Cyfip1 function in the corpus callosum showed that its deletion decreases the myelinating potential of oligodendrocytes [99].…”
Section: White Matter Alterationsmentioning
confidence: 99%